The Law of Fracture Evolution of Overlying Strata and Gas Emission in Goaf under the Influence of Mining. (12th August 2021) - Cheng, Cheng; Cheng, Xiaoyu; Yu, Rui; Yue, Wenping; Liu, Chao
Abstract : Mining is associated with poor safety due to pressure relief gas emission from the goaf during the production period. The aim of this study was to explore a case study of the Wangjialing coal mine 12322 working face in Shanxi, China, through physical simulation and field observation. The mine is characterized by overlying strata fracture in goaf during the process of working face mining. A mathematical model of gas source emission from the working face and gas migration and the finite element COMSOL software were used to simulate the law of gas migration in the region with overlying strata fissures under the influence of mining. The simulation results were used to explore the law of distribution of pressure relief gas in goaf. Rational parameters of the high-level directional long borehole for the pressure relief gas extraction in goaf were designed based on experimental results. The results showed that the development of the region with overlying strata fissures is affected by mining. In addition, the "trapezoid platform structure" is formed after fracture areas are connected. The maximum height of the stope caving zone was between 26.8 m and 28.1 m, and the maximum height of the fracture zone was approximately 110 m. The gas concentration exhibited a saddle-shaped distribution on the cut surface of the direction of the strike. Furthermore, the gas concentration showed an overall upward trend from the intake airflow roadway to the return airflow roadway and gradually decreased after reaching the maximum. In the vertical direction, gas concentration increased with the increase in the layer, and the position of the highest point of gas concentration gradually shifted to the direction of the intake airflow roadway. Construction parameters of the high directional long borehole were designed through simulation results. After steady extraction and stable extraction, the maximum gas concentration in the upper corner of the working face was 0.49%, and the maximum gas concentration in return airflow was 0.34%. The findings of this study provide information on the law of fracture evolution of overlying strata and gas migration in goaf under the influence of mining. These findings provide a basis for reducing gas overlimit in the working face or return airway corner, thus improving the safety production capacity of the coal mine.